Forensic Accounting vs Fraud examination: Roles, Importance and Differences (The Journal of Forensic Accounting Profession, 2022)
Fraud has existed throughout history. Yet, it is estimated that today's occurrence has a huge impact on global revenues, highlighting the importance of fraud examination and forensic accounting. Although the roles of the two disciplines appear to be similar (e.g. litigation support), they differ significantly in their objectives, with the goal of fraud auditing being to determine whether fraud has occurred and, if so, who is responsible. Forensic accounting has the additional objective of assessing the financial consequences and determining whether the allegations have a factual basis by analyzing the financial evidence.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2021-0007, pod licencom CC BY-NC-ND 4.0)
Keywords: Fraud Examination; Forensic Accounting; Fraud; Fraud Investigation